Projeto paranaense de civilização nas páginas da Revista Clube Curitibano (1890-1898) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
his research presents a historical study on the effervescence of the first decade of the Republic in Brazil, more specifically in Curitiba, with the objective of analyzing the disseminated ideas and the role played by Curitibano Club Magazine in the process of civilization, modernity and progress of society in Paraná. This study, whose object of research is the paraná project of civilization of the beginning of the First Republic (1890-1898), allowed us to defend the thesis that the civilization project, in the state of Paraná, was a liberal project taken over by symbolist educators and writers who disseminated it in the Curitibano Club Magazine. As a primary source of data, the study used copies of the Curitibano Club Magazine from 1890 to 1898.The study answered the question: what liberalism principles were present in the publications of the Curitibano Club Magazine and how these principles influenced the civilization project built and disseminated by the collaborators of this journal? This research has a documentary and bibliographic character and was supported by a historical materialism epistemology. It included a review of the state of the art, review of the relevant bibliography to the thesis, survey, catalogue and content analysis of issues of the educational literary Curitibano Club Magazine (1890 - 1898) as well as content analysis of special commemorative editions of the years 1932, 1950, 1962, 1985 and 1996, using NVivo software. The specific objectives of the study were to analyze the economic, social, political and cultural educational materiality of Brazil and Paraná, showing the contradictions of liberalism and capitalism at the end of the 19th century. Another specific aim was to identify the circulation spaces of educators and literary symbolists from Paraná, in the years 1890 to 1898, in particular the Curitibano Club Magazine, in addition to demonstrate the role of the press, mainly the Curitibano Club Magazine, its collaborators and the Symbolist Movement in the first decade of the Republic and, analyze texts from the Curitibano Club Magazine considering as main categories of analysis: liberalism, education, civilization, progress and modernity. In this study, initially, the economic, social, political and cultural educational aspects of Brazil and the state of Paraná were analyzed during the transition period between the Monarchy and the Republic, without losing sight of the liberal ideas that permeated the establishment of the Curitibano Club in 1881. Next, the role played by the Paraná press was demonstrated, especially the role played by the collaborators of the Curitibano Club Magazine at the end of the 19th century, in the consolidation of the republican liberal ideas, and the contributions of the Symbolist Movement in the construction of the Paraná civilization project. Finally, the content of texts from the Curitibano Club Magazine was analyzed based on the main categories of analysis, identifying the principles of liberalism and the civilization project from Paraná published by the periodical, as well as the relevance of this magazine and the Curitibano Club Association as non-formal spaces for bourgeois education.
Keywords: Projeto liberal de civilização; Imprensa paranaense; Educação não formal; Clube Curitibano; Revista Clube Curitibano; Liberal project of civilization; Paraná press; Non-formal education; Curitibano Club; Curitibano Club Magazine; CNPQ::CIENCIAS HUMANAS::EDUCACAO